UNIVERSITY COMMUNITY SERVICE ENABLING OPTIMAL HIGH SCHOOL CURRICULUM-BASED ACTIVITIES - Zubaedah, Siti Yasmina; Rembulan, Glisina Dwinoor; Tannia, Tannia; Susilo, Sophia Reni; Martadina, Cindy; Shen, Elza Jiuni (Jurnal Pengabdian dan Kewirausahaan, 2025)
As one of the pillars of higher education institutions, community services provide opportunities for university lecturers to contribute and acquire knowledge. The main objective of this study is to provide detailed descriptions on how university-school collaborations as a mode for promoting engaged scholarship and improve students’ learning experiences. This article discusses university community service activities at two private high schools in the Jakarta area. The two high schools invited university faculty members as jurors to assess the students’ projects, which determined their final grades. Observations found that having university faculty members present to give student scores enabled the schools to optimize the mechanisms in place that defined graduation requirements. As jurors, the faculty members provided objective, science-based assessments and the necessary feedback for the students. In addition to interacting with university-level teachers, presenting in front of academic jurors allowed the students to gain perspectives on related topics and make sound improvements to their projects. Consequently, the schools can optimize their curriculum-based activities that not only extend the learning experiences of the students but also provide long-term improvements to the overall quality of education.